Artificial Intelligence Modules and Teacher Creativity in Student Engagement: Modul Artificial Intelligence dan Kreativitas Guru dalam Keterlibatan Siswa - Septian Dwi Anto; Misriandi Misriandi; Sri Imawati (Academia Open, 2026)
General Background: The rapid development of Artificial Intelligence (AI) has introduced new directions in elementary education, particularly in supporting deep learning through adaptive teaching modules. Specific Background: In practice, the use of AI in instructional design remains closely linked to teachers’ creativity in managing learning activities. Knowledge Gap: Existing studies often examine AI-based modules or teacher creativity separately, leaving limited understanding of their combined role in shaping student engagement in elementary schools. Aims: This study aims to examine the role of AI utilization in developing deep learning teaching modules together with teacher creativity in managing learning toward student engagement in South Bekasi elementary schools. Results: Using a quantitative causal associative design with multiple linear regression analysis, the findings indicate that teacher creativity shows a significant relationship with student engagement, while AI utilization alone does not demonstrate a statistically significant relationship. Simultaneously, both variables account for a substantial proportion of the variation in student engagement. Novelty: This study highlights the combined role of AI-based deep learning modules and teacher creativity as an integrated pedagogical construct rather than isolated factors. Implications: The findings suggest that AI-supported instructional planning requires creative pedagogical management by teachers to foster meaningful student engagement in elementary learning contexts. Highlights • Teacher creativity shows a significant statistical relationship with student engagement• AI-based deep learning modules alone do not demonstrate a significant relationship• Combined variables explain a large proportion of engagement variation in classrooms Keywords Artificial Intelligence; Deep Learning Modules; Teacher Creativity; Student Engagement; Elementary Education